2013
DOI: 10.3928/21650799-20130816-67
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Smoking Among Operating Engineers

Abstract: Although disparities in smoking prevalence between white collar workers and blue collar workers have been documented, reasons for these disparities have not been well studied. The objective of this study was to determine variables associated with smoking among Operating Engineers, using the Health Promotion Model as a guide. With cross-sectional data from a convenience sample of 498 Operating Engineers, logistic regression was used to determine personal and health behaviors associated with smoking. Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…This was contrary to findings of Patil et al, [9]. Another study found that 29% of operational engineers used to smoke cigarettes, which was more than that which was seen in the present study [10].…”
Section: Discussioncontrasting
confidence: 99%
“…This was contrary to findings of Patil et al, [9]. Another study found that 29% of operational engineers used to smoke cigarettes, which was more than that which was seen in the present study [10].…”
Section: Discussioncontrasting
confidence: 99%
“…In the US, although there are wide variations in previous studies, 23%-76% of current smokers are partnered with someone who smokes (dual-smoker couples) (Choi, Pohl, Terrell, Redman, & Duffy, 2013;Kendrick et al, 1995;Rohrbaugh, Shoham, Skoyen, Jensen, & Mehl, 2012;Severson, Andrews, Lichtenstein, Wall, & Zoref, 1995;Tidey & Rohsenow, 2009). While living with a smoking spouse is associated with becoming a smoker or relapsing after quit attempts, living with a non-smoker is also associated with quitting and making more quit attempts (Falba & Sindelar, 2008;Jackson et al, 2015;Venters et al, 1984).…”
Section: Introductionmentioning
confidence: 99%